Estrategias políticas para el tratamiento de las drogas ilegales en Colombia (2013)
ABSTRACT: During the 1990's, institutionality in Colombia was negatively affected by large drug-dealing cartels. It was in this context where the Plan Colombia was born. This plan was a strategy to recover institutionality, reduce illegal coca and poppy plantations, weaken the economy of illegal insurgent groups, and restore investor confidence. Today, 13 years after the implementation of the Plan, the amount of illegal plantations has decreased. However they are still present, the traffic and trade of psychoactive substances have evolved, and consumption has increased. Therefore, there is now an evident societal need for strategies which address these issues that truly lead to sustainable development. Likewise, the community requires actions aimed at preventing this issue and promoting the care, treatment, and rehabilitation of those affected by this reality while providing adequate healthcare services.